The Arabidopsis thaliana Nuclear Factor Y Transcription Factors - Zhao, Hang; Wu, Di; Kong, Fanying; Lin, Ke; Zhang, Haishen; Li, Gang (Frontiers in Plant Science, 2017)
Nuclear Factor Y (NF-Y) is an evolutionarily conserved trimeric transcription factor complex present in nearly all eukaryotes. The heterotrimeric NF-Y complex consists of three subunits, NF-YA, NF-YB, and NF-YC, and binds to the CCAAT-box in the promoter regions of its target genes to regulate their expression. Yeast and mammal genomes generally have single genes with multiple splicing isoforms that encode each NF-Y subunit. By contrast, plant genomes generally have multi-gene families encoding each subunit and these genes are differentially expressed in various tissues or stages. Therefore, different subunit combinations can lead to a wide variety of NF-Y complexes in various tissues, stages, and growth conditions, indicating the potentially diverse functions of this complex in plants. Indeed, many recent studies have proved that the NF-Y complex plays multiple essential roles in plant growth, development, and stress responses. In this review, we highlight recent progress on NF-Y in Arabidopsis thaliana, including NF-Y protein structure, heterotrimeric complex formation, and the molecular mechanism by which NF-Y regulates downstream target gene expression. We then focus on its biological functions and underlying molecular mechanisms. Finally, possible directions for future research on NF-Y are also presented.